Changes in inflammatory biomarkers in HCV-infected patients undergoing direct acting antiviral-containing regimens with or without interferon - Mascia, Claudia (PLoS One, 2017)
BACKGROUND AND AIMS: Increased levels of chemokine interferon-gamma (IFN-γ)-inducible protein-10 (CXCL10), soluble CD163 (sCD163) and soluble CD14 (sCD14) have been reported in HCV infection. The aim of this study was to compare, sCD163 and sCD14 levels in HCV-infected patients undergoing direct acting antiviral (DAA)-containing regimens with or without interferon (IFN). METHODS: sCD163, sCD14 and CXCL10 were longitudinally measured by ELISA in 159 plasma samples from 25 HCV-infected patients undergoing IFN-based treatment plus telaprevir or boceprevir and 28 HCV infected subjects treated with DAA IFN-free regimens. Twenty-five healthy donors (HD) were included as controls. RESULTS: At baseline CXCL10, sCD163 and sCD14 levels were higher in HCV-infected patients than in HD. CXCL10 and sCD163 levels were significantly decreased in responder (R) patients who achieved sustained virological response (SVR), with both IFN-based and IFN-free regimens, while they were persistently elevated in non-responders (NR) patients who stopped IFN-based treatments because of failure or adverse events. Conversely, sCD14 levels were apparently unchanged during therapy, but at the end of treatment the levels reached normal ranges. Comparing the two regimens, the extent of CXCL10 reduction was more pronounced in patients undergoing DAA IFN-free therapies, whereas sCD163 and sCD14 reduction was similar in the two groups. Interestingly, only in IFN-based regimens baseline sCD163 levels were significantly higher in NR than in R patients, while in the IFN-free treatment group also patients with high sCD163 plasma levels obtained SVR. At the end of therapy, even if the biomarkers were largely decreased, their levels remained significantly higher compared to HD. Only in the early fibrosis stages, sCD163 values tended to normalize. CONCLUSIONS: These results indicate that IFN-free regimens including newer DAA induce an early and marked decrease in circulating inflammatory biomarkers. However, the full normalization of biomarkers was not obtained, especially in patients with advanced fibrosis, thus underlying the need for a treatment in the early stages of HCV infection.